Empirische Untersuchung der Anglizismen im Deutschen am Material der Zeitung Die WELT (Jahrgänge 1994 und 2004) - Burmasova, Svetlana (Bamberger Beiträge zur Linguistik, 2010)
There are different (and even contradictory) opinions on the proliferation of anglicisms in the German language. Even experienced linguists can have a wrong impression about changes in the subsystem of anglicisms due to premature judgement, personal observations, intuitive evaluation or absolute numbers. An evaluation is almost impossible without being based on quantitative inquiries and can otherwise not be seen as more than an assumption or speculation. The present empirical study of English borrowings offers a firm foundation for statements discussing the usage and spreading of anglicisms in German, because it shows the dynamics of the borrowing-process during two time-periods (1994 - 2004 and 1954 - 1964). Hence the work presented deals with the current development of the '90's and 2000's in comparison with a previous study of B. Engels (1976) concerning the time-period 1954 - 1964, thus showing a diachronic overview of 50 years, from the post-war-period until today. To describe the borrowing-process from English, two statistic values were chosen: the average and the dispersion of relative frequencies, whereby the first value is represented as revealing the quantity and the second as revealing the quality. The mentioned values complement one another and give a more thorough picture on the use of anglicisms: The quantitative values indicate an increasing use, while the dispersion as well as the comparison with the reference-study of B. Engels show that today the use of already borrowed anglicisms is much more common than the creation of new borrowings, which illustrates stabilization in usage patterns and could indicate a form of integration. In this sense, the work presented offers a different point of view on integration, which does not consider (only) formal changes of single anglicisms. The study is based on relative numbers which will enable comparison with further studies. Another question of interest concerns the subject areas in which the greatest influence of English on German can be seen as well as the dimension of this influence. It has been shown that the usage of English words in German varies from subject area to subjet area. It's remarkable that a growing use of anglicisms is seen in all subject areas, except for "science and technology". The strongest growth - by a factor of three - lies in the economics section. Furthermore the study disproves some mistaken conclusions, for example one that states that anglicisms do not appear frequently considering that according to numerous analyses they only occupy 1% of a text. This claim is inaccurate, because in fact this rate is quite large for a linguistic phenomenon. Another statement concerning the fact that more nouns than other words are borrowed from English is only correct when applied to absolute numbers. The speed of growth of all studied lexical categories is almost equal. All results of this work are to be taken under reserve, as far as they are not to be seen as absolute but as quantitative tendencies.